Betaleukin in therapy of chronic hepatitis C - E. S. Romanova; N. I. Kuznetsov; G. Yu. Startseva (Журнал инфектологии, 2014)
The article presents the problems of modern antiviral therapy of chronic hepatitis C. The effectiveness of combined therapy with pegylated interferon and ribavirin in patients infected with 1st genotype is not more than 50%. Inclusion in the therapy HCV’s protease inhibitors (telaprevir and boceprevir) increases the sustainable virological response in patients with the 1st genotype, but this treatment is more expensive and accompanied by more serious complications. There is a large group of patients in Russia, who can’t have got such treatment because of its high cost. The results of clinical studies in application of betaleukin (recombinant IL-1β) in combined antiviral therapy of chronic hepatitis C also are analyzed.